2018
DOI: 10.1111/ejss.12543
|View full text |Cite
|
Sign up to set email alerts
|

Climate and soil moisture content during development of the first palaeosol in the southern Loess Plateau

Abstract: Summary The scientific problems concerning Quaternary soil water content and the water cycle have not been researched. This study examined the soil water content and depth of distribution of gravitational water in the south Loess Plateau during development of the first palaeosol layer (S1) by methods such as field investigation, electron microscopy, energy spectrum analysis, chemical analysis, and so on. The purpose was to reveal the climate, water balance and vegetation type at the time when S1 developed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…It is noticeable that the extreme values do not exactly correspond to 76.8 ka B.P., as the transition from PZ-I to PZ-II occurred at about 76.5 ka B.P., and lagged several hundred years after the cooling event. This result approximately agrees with a number of previous studies [49,50].…”
Section: Pollen Type and Its Environmental Significancesupporting
confidence: 93%
“…It is noticeable that the extreme values do not exactly correspond to 76.8 ka B.P., as the transition from PZ-I to PZ-II occurred at about 76.5 ka B.P., and lagged several hundred years after the cooling event. This result approximately agrees with a number of previous studies [49,50].…”
Section: Pollen Type and Its Environmental Significancesupporting
confidence: 93%
“…The soil water conditions can also be expressed by chemical elements [14]. In the southern CLP, the red ferri-argillans and migration of CaCO 3 and S r of S1 indicated that the paleo-climate of the last interglacial was subtropical and humid and the soil water balance was positive [15]. These results confirmed that S1 is appropriate for studying the effect of climate on pedogenesis and soil hydraulic properties.…”
Section: Introductionmentioning
confidence: 67%
“…During the pedogenic processes, soil systems stored large amount of information about environmental factors. Such as red ferri-argillans and Sr contents, these proxies revealed that in the southern CLP, the soil water balance was positive during the last interglacial, and the southern CLP was under a humid subtropical paleoclimate [15]. This mechanism was named "soil memory" [49].…”
Section: Pedogenesis and Soil Water Propertiesmentioning
confidence: 99%